2010
DOI: 10.1111/j.1467-9515.2009.00706.x
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Weak Architecture: The French Ministry of Health

Abstract: International audienceThis article asks whether the public administration of health in France fits the general description of French state institutions as autonomous, powerful bureaucracies. Existing sources on the French Ministry of Health indicate that three types of processes have shaped its institutional structure, its official mandate and its actual policy influence since its inception in the 1920s. Faced with the rise of private-practice medicine, the Ministry first emerged as a resource-poor institution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…As a result, capacity assessments often respond to the needs of individual projects and do not address wider organizational issues, fail to address the unique institutional opportunities and constraints that universities face, and focus on ‘capacity needs’ with less attention to existing strengths or ‘capacity assets’. While studies exist considering the capacity of ministries of health and independent entities ( Briatte 2010 ; Greer 2010 ; Bennett et al 2012b ), work has only recently begun to explore the HPSR+A capacity of universities, typically within regional networks such as ASPHA (Association of Schools of Public Health in Africa). The existing work in Africa appears also to focus on research capacities ( Simba 2012 ), and we found no assessments of universities’ capacity related to HPSR+A teaching and networking.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, capacity assessments often respond to the needs of individual projects and do not address wider organizational issues, fail to address the unique institutional opportunities and constraints that universities face, and focus on ‘capacity needs’ with less attention to existing strengths or ‘capacity assets’. While studies exist considering the capacity of ministries of health and independent entities ( Briatte 2010 ; Greer 2010 ; Bennett et al 2012b ), work has only recently begun to explore the HPSR+A capacity of universities, typically within regional networks such as ASPHA (Association of Schools of Public Health in Africa). The existing work in Africa appears also to focus on research capacities ( Simba 2012 ), and we found no assessments of universities’ capacity related to HPSR+A teaching and networking.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the pioneering nature of our study, we cannot compare our findings with similar research in developing countries. However, the complexity of applying MOH capacity to health policy processes is shown in some European contexts (Mätzke, , Briatte, , Greer, ).…”
Section: Discussionmentioning
confidence: 99%
“…Attempts have been made to apply the notion of capacity in relation to strengthening health systems (LaFond et al ., , Pappaioanou et al ., ) or conducting health systems and policy research (Bennett et al ., , Gonzalez Block and Mills, ) and to better understand the role of health ministries in health policy processes in some European contexts (Briatte, , Mätzke, , Greer, ). However, we found no frameworks that focus on capacity to conduct health policy processes in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…In the same way, vertical policy -i.e., European Court of Justice decisions -paved the way for a horizontal policy that made policy more coherent by giving the EU institutions a greater warrant to intervene in health care services policy, among other things (Hervey and Vanhercke 2010). (Radin 2010), other US agencies (Roberts 2006), or the health ministry of an EU member state (Mätzke 2010;Briatte 2010).…”
Section: Policymentioning
confidence: 99%